2011
DOI: 10.1364/ao.50.000387
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic chips for a surface plasmon resonance instrument

Abstract: In this work we have replaced a commonly used Au film with an Au/Ag bimetallic film working as the sensing chip in the commercial surface plasmon resonance (SPR) instrument, Biacore 3000. The bimetallic chip gives out sharper SPR dip than that by the chip made of an Au film. The applicability and stability of the bimetallic chip on the Biacore 3000 are tested by real-time monitoring of biological coupling processes between sulfamethoxazole (SMX) and anti-SMX, which is useful in rapid detection of contamination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Thus, gold coating thickness is kept as 2 nm in order to satisfy both sensitivity and surface chemistry requirements. Apart from the previous studies which use the Ag/Au bimetallic structure to increase sensitivity [16][17][18][19][20], we used this configuration to obtain a response below 520 nm which is not possible with the commonly used single gold layered couplers.…”
Section: Design and Fabrication Of Spri Sensor Chipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, gold coating thickness is kept as 2 nm in order to satisfy both sensitivity and surface chemistry requirements. Apart from the previous studies which use the Ag/Au bimetallic structure to increase sensitivity [16][17][18][19][20], we used this configuration to obtain a response below 520 nm which is not possible with the commonly used single gold layered couplers.…”
Section: Design and Fabrication Of Spri Sensor Chipsmentioning
confidence: 99%
“…We employed a silver/gold (Ag/Au) bilayer structure coated on the periodic corrugations of Blu-ray discs in order to perform plasmon resonance imaging at the central region of visible spectrum ( r ∼500 nm) under normal incidence illumination in aqueous environment. This allowed the optimal use of the CMOS sensor of the smartphone while maintaining high sensitivity, chemical stability and biological affinity [16][17][18][19][20]. A microfluidic channel is placed on the bimetallic layer for controlled plumbing of the liquids.…”
Section: Introductionmentioning
confidence: 99%
“…Gold has the advantage of high chemical resistance and is used as the upper layer. Chen et al [4] confirmed the enhanced performance of such films using a commercial Biacore instrument. Au/Ag composite layers provide a higher SNR compared to gold monolayers of the same total thickness.…”
Section: Introductionmentioning
confidence: 90%
“…The formation of such a wave at the metal-analyte interface enables PSPR sensors to be highly sensitive to changes in the refractive index of an analyte. Therefore, PSPR sensors have been extensively applied in several fields including biology, genetic engineering, and biochemistry [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The second category comprises localized surface plasmon resonance (LSPR) sensors that have no propagation capability.…”
Section: Introductionmentioning
confidence: 99%